Craterispermum capitatum and C. gabonicum (Rubiaceae): two new species from the Lower Guinean and Congolian domains - Taedoumg, H.E.; Sonke, B.; Hamon, P.; Block, P. de (Pensoft Publishers, 2017)
Craterispermum capitatum and C. gabonicum, two new species of Rubiaceae, are described from the Lower Guinea and Congolian Domains. Detailed descriptions and distribution maps are provided for each species, their conservation status is assessed and their taxonomic affinities are discussed. Craterispermum gabonicum is unique within the genus because of the strong dimorphism in brevistylous and longistylous flowers and inflorescences. We hypothesize that this species shows some form of dioecy. The distribution of C. capitatum shows a wide disjunction: the species is present in the Lower Guinean and Congolian Domains but absent from Gabon and South Cameroon. An identification key for the Craterispermum species present in the Lower Guinean and Congolian Domains is given.